Cardiovascular adaptation to the Fontan circulation. (10th August 2017) - Veldtman, Gruschen R.; Opotowsky, Alexander R.; Wittekind, Samuel G.; Rychik, Jack; Penny, Daniel J.; Fogel, Mark; Marino, Bradley S.; Gewillig, Marc
Abstract: Although medium‐term survival following Fontan operations in the modern era has improved dramatically, late cardiovascular and extracardiac morbidity are common and are associated with impaired quality of life and premature late mortality. This serves as a reminder of the extraordinary adaptations required of the cardiovascular system when the systemic arterial, systemic venous and pulmonary circulations are placed in series coupled to a single ventricular pump. This article reviews the key features and principles that govern interactions between the ventricle, systemic arterial circulation, the systemic venous and pulmonary circulatory compartments, the microcirculation, and lymphatic circulations. The overarching aim is to provide insight into the integrative pathophysiology that governs the Fontan circulation and stimulate thoughtful approaches to advance research.